Parametric analysis of ball milling condition on thermoelectric performance of Bi0.6FeCo3Sb12 skutterudite. (29th August 2018) - Raihan, Ovik; Mohd Said, Suhana; Sabri, Mohd Faizul Mohd; Rozali, Shaifulazuar; Long, Bui Duc; Kimura, Kaoru; Tobita, Kazuki; Fitriani,; Mohd Salleh, Mohd Faiz; Ali Bashir, Mohamed Bashir
Abstract: The FeCo3 Sb12 skutterudite crystal was doped with Bi to act as a filler material for the Bi0.6 FeCo3 Sb12 formulation. It was prepared by ball milling and spark plasma sintering. The microstructure and thermoelectric performance of the bulk skutterudite was evaluated as function of its mechanical alloying process, i.e. ball milling. Rietveld analysis of its XRD spectra indicated that The Bi doping on the Co4 Sb12 based skutterudite succeeded in partially filling the voids of the skutterudite, whilst the Fe doping partially substituted the Co sites in the lattice. This serves to simultaneously increase the electrical conductivity whilst reducing the thermal conductivity of the resulting skutterudite. The ball milling times was correlated to the resulting microstructure, and ultimately, its thermoelectric performance. It was found that the moderate milling times (at 15 h) resulted in the best electrical conductivity, given the homogenous distribution of particles. A Maximum ZT value was observed 0.18 for 10 h ball milled sample at 673 K, whilst almost the same value was achieved for the 15 h ball milled sample, i.e. ZT = 0.17 at 673 K. Beyond this milling time, agglomeration of particles after ball milling caused degradation in the overall thermoelectric performance. Thus, this paper presents a strategy optimize the mechanical alloying process parameters to provide improved thermoelectric performance.